2020
DOI: 10.1097/md.0000000000019120
|View full text |Cite
|
Sign up to set email alerts
|

Network and pathway-based analyses of genes associated with osteoporosis

Abstract: Osteoporosis (OP) is a disease characterized by bone mass loss, bone microstructure damage, increased bone fragility, and easy fracture. The molecular mechanism underlying OP remains unclear. In this study, we identified 217 genes associated with OP, and formed a gene set [OP-related genes gene set (OPgset)]. The highly enriched GOs and pathways showed OPgset genes were significantly involved in multiple biological processes (skeletal system development, ossification, and osteoblast dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 97 publications
1
10
0
Order By: Relevance
“…Furthermore, the mitogen-activated protein kinase (MAPK) signalling pathway was enriched, which is also very important for skeletal development and, in particular, for chondrogenesis [ 92 ]. These observations are in accordance with recent results from pathway analyses [ 25 , 93 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the mitogen-activated protein kinase (MAPK) signalling pathway was enriched, which is also very important for skeletal development and, in particular, for chondrogenesis [ 92 ]. These observations are in accordance with recent results from pathway analyses [ 25 , 93 ].…”
Section: Discussionsupporting
confidence: 93%
“…Rab27a interference rescued dysfunctional osteoblasts originating from OVX mice and was restrained by miR-124 to attenuate osteoclastogenesis (42,43). Moreover, previous studies have shown that Hyal1 expression is upregulated via osteoclast formation and that Serpine1 is enriched in osteoporosis patients (44,45). In addition, Antxr1 is also involved in RANKL-induced osteoclastogenesis (46).…”
Section: Discussionmentioning
confidence: 98%
“…Among adults, a small male predominance of HPI-related outcomes has been found in a meta-analysis based on 169 studies (OR 1.12, 95% CI: 1.09, 1.15) [ 407 ]. Shared genetic basis underlying OP and a variety of HPI-related chronic extra-gastroduodenal diseases (CAD, DM, dyslipidemia) has been reported [ 408 , 409 , 410 , 411 , 412 , 413 , 414 , 415 , 416 , 417 , 418 , 419 ]. The shared biology and bi-(multi-)directional links between OP and HPI-associated chronic diseases apply particularly to CVD, CKD, CLD, DM and neurodegenerative diseases; these disorders are interrelated and often accompanied by OP/OF [ 420 , 421 , 422 , 423 , 424 , 425 , 426 , 427 , 428 , 429 , 430 ], and the risk of OP/OF increases when two or more HPI-associated chronic diseases are present.…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%